PERSPECTIVES OF INORGANIC COMPOUNDS APPLICATION FOR ELECTROPLATING INDUSTRY WASTEWATER TREATMENT - КИСЛОВА, О. В.; ПАТЛУН, Д. В. (Technologies and Engineering, 2024)
Purpose. Analysis of modern chemical technologies for electroplating industry concentrated effluents and washing wasterwaters treatment; generalization of the peculiarities of inorganic substances using for the wastewater purification. Methodology. Analytical review of scientific and scientific-practical literature for the systematization of inorganic compounds application for galvanic industries cyano- and chromium-containing wasterwaters treatment, precipitation of heavy metal ions, neutralization of pH wastewaters. Findings. Mineral acids and alkalis for neutralization, oxidizers (liquid chlorine, chlorinated lime, calcium or sodium hypochlorite, ozone, potassium permanganate, hydrogen peroxide), reducing agents (sodium sulfite, sodium hydrogen sulfite, sodium thiosulfate, iron (II) sulfate), as well as hydroxides, carbonates, sulfides for precipitation of heavy metal ions are widely used for electroplating industry wasterwaters decontamination. The advantages of the reagent method include universality, ease of operation, use of inexpensive equipment, a wide range of initial ion concentrations, the possibility of joint treatment of wastewaters from various galvanic processes after toxic cyano- and chromium-containing wasterwaters purification. The main task is to improve reagent wastewaters treatment methods with the aim of reducing of chemical compounds using, increasing the completeness of metal ions and other harmful substances extraction, simplifying their subsequent separation from sludge for complete utilization. Originality. The optimal conditions for the inorganic compounds application for the electroplating industry wasterwaters treatment are substantiated, implying the need to take into account the characteristics of the specific galvanic production effluents, such as the concentration of pollutants, pH values, the presence of additional compounds in the electrolytes composition and other factors. Practical value. The directions of electroplating industry wastewater treatment by the reagent methods are summarized, the main inorganic compounds used for the concentrated effluents and washing waters treatment and the optimal conditions for their use are characterized.